The policy implementation costs and occurring mechanisms of bargaining among different levels of the Chinese governmental hierarchy: A case analysis of the prohibition of grazing in Sidong County. (July 2019) - Feng, Meng
Bargaining is a significant form of interaction between different levels of the Chinese government. Therefore, the mechanism of bargaining is suggested as a representative operational model for understanding the behaviors of local governments in the hierarchical system of government. This paper describes in detail several rounds of bargaining between superior and subordinate government officials in the process of implementing a policy prohibiting grazing in Sidong County. The policy was made at the county level. Township-level governments chose to bargain with their superior due to the difficulty of implementation in the early stages but failed. Strict implementation then led to frequent conflicts between local government and farmers. The township level of government instantly turned to bargaining with the county level and used a confrontational strategy to successfully obtain more freedom for implementation. This paper uses the theoretical framework of implementation costs analysis to illustrate the functioning mechanism of bargaining behavior. The different combinations of implementation costs cause township-level governments to choose or adjust to different methods. The high cost of implementation processes allows the township-level government to use bargaining as the only reasonable method of implementation. The process of bargaining indicates that township-level governments improve bargaining ability relative to strict requirements for implementation of policy and intensifying social conflicts. The essential features of bargaining in policy implementation among different levels of the Chinese governmental hierarchy are: no deadlock implementation; agreement point swings from side to side; and alternating occurrences between short-run equilibrium and bargaining.